MEDIA SOSIAL DI KALANGAN KOMUNITAS GAY ( STUDI KASUS TENTANG AKTIVITAS MEDIA SOSIAL KELOMPOK GAY DI PEKANBARU ) - Nurefni "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research was done in the city Pekanbaru. The sampling methode using purposive sampling methode Where researchers took samples to determine in advance the number of samples to be taken. One informant willing to be interviewed and have a network of social media then one informant affiliated to a group or gangster srik lovers consisting of six people who then of six people who then also willing to be interviewed so as to collect research data determined several informants. In this study researchers set six informant which is derivedfrom the alley srik lovers which consists of six people who are gay including groups that exist in pekanbaru. The existence of homosexuality is a social phenomena that exists around indonesian in general, including those of the city Pekanbaru. Problems faced by homosexuals today is how to put themselves in the life of society. Because of their presence are still in said foreign in life and a little difficult to accept. Many people widely assumed to be a homosexual only be a disgrace to disgrace themselves and the families of people who were in the vicinity. But the reality of homosexsuals are increasingly showing their presence by establhising a set of some people to form a community of social media networks so that their existence is increasingly showing his identity. Then more open acsess social media as a platform for the city’s gay community Pekanbaru also gives color gay openness to the general public. Although gays are still considered taboo by society but this circle more confirms his or her identity the wide variety of specialized online social media as a platform where friendship gay meeting to matchmaking in these circles. As for social media in use such as Grindr, badoo, tagged, jack’d and scruff. Keywords : Social media, Group, Gay